Vengeance is mine : a Red River mystery - Wortham, Reavis Z. (Wortham, Reavis Z. Red River mystery, 2014)
In October of 1967, the Summer of Love is history, rock and roll is dark and revolutionary, and people in the small east Texas community of Center Springs simply want to live their lives as quietly as possible. But a handsome darkness in the form of Las Vegas gangster Anthony Agrioli has left the business to hide out in their tiny backwater settlement with his blond bombshell girlfriend. Two years earlier, Agrioli met newlyweds Cody and Norma Faye Parker in a Vegas casino and heard their enthusiastic descriptions of the perfect place to settle down and raise a family. At least it was perfect, before their peaceful world found itself in the crosshairs of a coming confrontation. Back in Center Springs, thirteen-year-old Top Parker has what his grandmother, Miss Becky, calls a poisoned gift: his dreams, though random and disconnected, always seem to come true. This time Top dreams he's a wagon hub with spokes converging from all directions. To him, the spokes symbolize that something is coming. He doesn't know their quiet community will soon be a combat zone when the gangsters arrive. But they're after something else, not Agrioli -- yet. A sheriff crooked as a dog's hind leg, an unsolved murder in the river bottoms, counterfeit money, and a bank robbery all wrapped in a country Shakespearean comedy once again bring together Constables Ned and Cody Parker, Deputy John Washington, Judge O. C. Rains, and the rest of Wortham's real and sometimes wacky cast of characters.